TALFIQ SEBAGAI SALAH SATU METOD PENYELESAIAN HUKUM DI INSTITUSI-INSTITUSI KEWANGAN ISLAM DI MALAYSIA: SUATU ULASAN LITERATUR: Talfīq As A Legal Solutions in Islamic Financial Institutions in Malaysia: A Literature Review - Jamaludin, Mohd Hafiz; Buang, Ahmad Hidayat (Jurnal Syariah, 2019)
Talfīq is widely used by the present Islamic scholars in formulating current laws, especially in the field of Islamic finance. In this article, the researcher has reviewed a number of published articles with the purpose to analyze several matters which possess direct relationship with the concept of talfīq and its application in the field of Islamic finance. The researcher had deliberately elaborate the concept of talfīq and the debates by scholars, as well as the applications on this concept. Besides that, the researcher also explained the concept of Shariah supervision, the Shariah Advisory Council (SAC) of Bank Negara Malaysia and the legal solutions methods employed by the Shariah supervision body of Islamic financial institutions from the studies done by the previous researchers. This study reveals that the studies on talfīq including the ruling of its usage as a legal solution method need to continue in order to complete the understanding on this concept. Furthermore, specific studies on legal solution method in Islamic financial institutions need to be carried out so as to produce a specific legal solution method to be used as a guide to the Shariah supervision body of Islamic financial institutions currently.